KONSEP DAN STRATEGI EFEKTIVITAS KEPEMIMMPINAN PENDIDIKAN MASA DEPAN - Noer Rahmah (LP3M IAI Al-Qolam Malang, 2014)
In rapid change era, in which all aspects that affect the development of the organization is very great, educational organizations face with variety of critical challenges. These challenges collectively require organizations to build new capabilities. One of the most crucial component for the success of future education organization is a leader. Educational organizations require leadership figure who is able to think ahead, to anticipate any changes and current development. Therefore the future organizations to be able to must have a clear and focused vision. Its leaders must have prominent competence for the sake of facing environmental changes. They also should have some effective strategies because the future of education requires the figures of the ideal leader who can bring significant changes.Keywords: educational leadership, strategy, effectiveness